2021
DOI: 10.1017/cts.2021.836
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Clinical Research Units (CRUs)

Abstract: Few studies have explored the challenges that the COVID-19 pandemic has presented for Clinical Research Units (CRUs), the solutions that have been implemented, and the changes that have been made in the operational guidelines for these entities. This study sought to identify and document common practices implemented by CRUs around the United States of America (USA) when addressing the unique challenges posed by the COVID-19 pandemic. This descriptive study utilized a non-experimental mixed-methods approach and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Projects′ experiences raised questions about what research activities do, or should, count as essential. A study of clinical research units across the US reported a general definition of essential research as “research that is essential to a participant′s health and/or well‐being,” (Subramain et al, 2021 ) but the experience of the CSER projects suggests that this definition was not always straightforward to apply in practice, particularly in the setting of a nationwide research consortium. Projects took place in a range of clinical contexts, and recruitment during COVID was affected by changes in which patients were able to attend clinical visits as well as decisions about whether the research itself should continue.…”
Section: Discussionmentioning
confidence: 99%
“…Projects′ experiences raised questions about what research activities do, or should, count as essential. A study of clinical research units across the US reported a general definition of essential research as “research that is essential to a participant′s health and/or well‐being,” (Subramain et al, 2021 ) but the experience of the CSER projects suggests that this definition was not always straightforward to apply in practice, particularly in the setting of a nationwide research consortium. Projects took place in a range of clinical contexts, and recruitment during COVID was affected by changes in which patients were able to attend clinical visits as well as decisions about whether the research itself should continue.…”
Section: Discussionmentioning
confidence: 99%
“…This decision resulted in overlooking these units from any discussion related to translational science. To re-establish dialogue between CRUs that would help units benchmark and improve operations, the Research Unit Network (RUN) was created with the express purpose of enabling direct communication, In addition to facilitating discussions around the topics mentioned already, RUN was pivotal in exchanging information and practices during the beginning of the COVID-19 pandemic [3]. This experience resulted in the identification of the unique roles played by CRUs as part of a disaster response.…”
Section: Research Unit Networkmentioning
confidence: 99%
“…In addition to facilitating discussions around the topics mentioned already, RUN was pivotal in exchanging information and practices during the beginning of the COVID-19 pandemic [3] . This experience resulted in the identification of the unique roles played by CRUs as part of a disaster response.…”
Section: Introductionmentioning
confidence: 99%
“…This included planning and/or implementation of reopening of research activities, primarily for clinical research with lesser involvement for the development and implementation of policies for basic research across all sites. CTSA-supported CRUs played key roles in administering and supporting COVID-19 and vaccine trials [53], including their significant contribution in Phase 3 trials for the Pfizer and Moderna vaccines, the first two vaccines authorized for use in the US.…”
Section: Flexible Forward-looking Decision-making and Governancementioning
confidence: 99%